Aquacultural importance of the integumental pore pattern in postlarval whiteleg shrimp Litopenaeus vannamei (Decapoda: Penaeidae) - Cabrera-Jiménez, Jorge Alberto (Revista de Biología Tropical, 2006)
The analysis of integumental pore pattern has identified two intraspecific groups of postlarval shrimp Litopenaeus vannamei (Boone, 1931), a species of which three to five natural populations or groups are expected to be found from Mexico to Perú. Natural distribution and man-made redistributions have not been typified on a population basis in any penaeid, but it is important to do so in this commercially significant group. Important factors to be defined on a geographic population or group basis include differences in domesticity (eg resistance to pathological agents); food conversion indexes and food preferences, growth indices, tolerance to stress of various origins and other attributes useful in aquaculture. This consideration is valid not only for L. vannamei but also for any other shrimp species that has been the object of artificial redistribution.